Pengaruh Persistensi Laba Terhadap Earnings Response Coefficient Dengan Fleksibilitas Keuangan Sebagai Variabel Moderasi - Saputra, Dwi; Sunarto, Sunarto (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2022)
The purpose of this research is to examine the effect of earnings persistence on earnings respon coefficient (ERC) with financial flexibility as moderating variable. Mining sector companies listed on the Indonesia stock exchange (IDX) for the period 2017-2019 make up the population with 27 data samples using purposive sampling. The annual financial report becomes secondary data in this research. Multiple linier regression analysis and Moderated Regression Analysis (MRA) is the study methods that the researches uses. The result of this research that earnings persistence had a significant effect on earnings response coefficient (ERC), and flexibility financial is weaken the effect of earnings persistence on earnings response coefficient (ERC).